016 Long-term efficacy and safety of perampanel in elderly patients from phase III open-label extension studies. Issue 6 (27th May 2022) - Marawar, Rohit; Leppik, Ilo E; Wechsler, Robert T; Patten, Anna; Ngo, Leock Y; Malhotra, Manoj
Abstract : Background: The long-term efficacy and safety of adjunctive perampanel was evaluated in patients aged ≥60 years with focal-onset seizures (FOS) with/without focal to bilateral tonic-clonic seizures (FBTCS) who participated in open-label extension Studies 307 (NCT00735397 ) and 335 (NCT01618695 ). Methods: Patients received perampanel 2–12 mg/day during Studies 307 (16-week blinded Conversion; 256-week Maintenance) and 335 (4-week Pre-conversion; 6-week Conversion; ≥46-week Maintenance). Assessments included median per cent reduction in seizure frequency/28 days vs pre-perampanel baseline, 50% responder rates and treatment-emergent adverse events (TEAEs). Results: The Safety Analysis Set included 71 patients (mean age, 64.0 years). Seizure frequency reductions during Years 1 and 2 were 31.7% (n=71) and 44.5% (n=38) (total FOS), and 95.5% (n=19) and 100.0% (n=9) (FBTCS), respectively. Seizure frequency reductions were observed during Years 3/4 (low patient numbers); over one-third of patients achieved a ≥50% seizure reduction each year. During Years 1, 2, 3 and 4, TEAE incidence was 87.3% (n=62/71), 60.4% (n=29/48), 47.4% (n=9/19) and 57.1% (n=8/14), respectively; most common were dizziness and fall during Years 1/2 and 3/4, respectively. Conclusion: Perampanel was associated with reductions in seizure frequency over 4 years in elderly patients. The safety profile was consistent with the overall populations. Funding: Eisai Inc. stella_ngo@eisai.com 33